2017
DOI: 10.1245/s10434-017-5885-4
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging in Stage IV Pancreatic Cancer: A New Population Eligible for Surgery?

Abstract: Patients with mPDAC who were fully responsive to nCT may be cautiously considered for surgery, with potential benefit in survival compared with palliative chemotherapy alone. This is supported by results of our retrospective study, which is the largest ever reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
125
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 20 publications
2
125
0
4
Order By: Relevance
“…A common feature of both the Heidelberg study and the European registry is that only a minority of patients underwent neoadjuvant therapy before LM resection was performed. By contrast, three other reports showed much longer survival rates when all of the analyzed patients received neoadjuvant therapy prior to undergoing resection [42][43][44]. This observation is certainly explained by the selection effect of neoadjuvant treatment, which is exemplarily shown in the study by Crippa et al [42].…”
Section: K Main Topicmentioning
confidence: 83%
See 1 more Smart Citation
“…A common feature of both the Heidelberg study and the European registry is that only a minority of patients underwent neoadjuvant therapy before LM resection was performed. By contrast, three other reports showed much longer survival rates when all of the analyzed patients received neoadjuvant therapy prior to undergoing resection [42][43][44]. This observation is certainly explained by the selection effect of neoadjuvant treatment, which is exemplarily shown in the study by Crippa et al [42].…”
Section: K Main Topicmentioning
confidence: 83%
“…Although only 11 patients eventually underwent metastasectomy in this collective, survival was impressively high when multiagent chemotherapy was used, the number of resected metastases did not exceed five lesions, and CA 19-9 levels showed a reduction of >50% during neoadjuvant therapy. Interestingly, in one study from Verona, patients with hepatic metastases had exploration laparotomy after preoperative chemotherapy and underwent isolated primary tumor resection only in cases with complete intraoperatively vanished liver lesions, and therefore did never receive hepatectomy [43]. Still, the resulting median OS in these 24 patients was 13 months after pancreatic resection and 56 months after the initial diagnosis of metastases.…”
Section: K Main Topicmentioning
confidence: 99%
“…11 Increasing evidence has suggested that neoadjuvant chemotherapy may improve outcomes in pancreatic cancer. [15][16][17][18][19][20][21] To receive full doses of neoadjuvant chemotherapy, patients with obstructive jaundice may undergo preoperative ERCP. However, in this analysis, patients who did not receive a preoperative ERCP appeared more likely to receive neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] More recent studies have suggested that patients may have improved outcomes with neoadjuvant therapy before resection. [15][16][17][18][19][20][21] Therefore, more pancreatic cancer patients may receive preoperative ERCP, particularly those with borderline resectable tumors.…”
mentioning
confidence: 99%
“…It is rational to include our case clinical course within the PDAC phenotype identified by Frigerio et al, in which the complete response obtained on liver metastases to a first line cytoreduction, might predict a favorable clinical outcome with a median overall survival (OS) of 56 months for 24 out of 535 subjects (4,5%) bridged to surgery. The regimen employed was either FOLFIRINOX (66%) or gemcitabine-based therapy (34%) [15], leading to 88% of R0 resection and to 17% of patients gaining a complete pathological response. The mortality rate was 0%.…”
Section: Discussionmentioning
confidence: 99%